Bradykinin and electrical stimulation increase prostaglandin production in the rat vas deferens - Peredo, Horacio Angel (2001)
The epididymal portion of the rat vas deferens produced prostaglandins (PG) E2, F2αand 6-keto F1 α. Electrical stimulation (ES, 0.1 Hz, 1 ms) increased such production by 100%, and similar results were obtained in the presence of 1.0 μM bradykinin (Bk). When both stimuli were applied simultaneously, the increases in PG production were 1100% for PGE2, 800% for PGF2αand 400% for PG6-keto F1 α. Prazosin abolished the effect of ES on PG production. A selective Bk B2-receptor antagonist abolished the increase in PG production induced by Bk, both in non-stimulated and in ES tissues. Bk (1.0 μM) elicited contractile responses in non-stimulated as well as in ES tissues, responses that were not modified in the presence of 10 μM indomethacin. In conclusion, the effects of Bk on prostaglandin production appears to depend on the activation of B2receptors, while the increase in prostaglandin release induced by ES, and the effects observed with both stimuli simultaneously, should be mediated by the release of noradrenaline and the subsequent activation of α1adrenoceptors.